Abstract 4147462: Ambulatory Breath Analyzer for Measuring Cardiac Output - Hale, Joshua; Kolomenski, Alexandre; Schuessler, Hans; Tong, Carl (Circulation (New York, N.Y.), 2024)
Background: Knowing heart failure patients' cardiac output at outpatient setting can guide optimization of medical therapy and detect decompensation early to trigger timely response; therefore, following patients' cardiac output has potential to greatly improve care of heart failure patients. Unfortunately, an easy to use ambulatory device that can measure cardiac output at patients' homes currently does not exist. Hypothesis: One can derive cardiac output by measuring carbon dioxide (CO2) and flow of exhaled breath because right heart delivers CO2 laden blood to the lungs, right heart = left heart in blood flow. Method: We made a novel breath analyzer that measures cardiac output from exhaled breath. This device uses [CO2] and volume of exhaled breath as input. Exhaled flow rate of CO2 is measured, then divided by the difference between venous and arterial [CO2]. The difference is calculated from exhaled CO2 input to a novel formula. We built and tested a prototype to implement this method. We designed a heated breath flow path with baffles to combat the high humidity in breath. Custom software then calculates cardiac output in real time. We used this prototype to measure the cardiac output at rest and after set pace treadmill jogging. Results: The prototype (fig) featured small dimensions, light weight, and compatibility with a typical laptop computer. Reliability testing showed a 1.85% standard deviation in volume detection over 70 test breaths. Carbon dioxide detection was compared to high-sensitivity cavity ringdown spectroscopy with an error of 1.14%. Measurement of cardiac output was performed on 11 human volunteer subjects. Echocardiogram of stroke volume X heart rate was used as reference. Cardiac output measurements from our device correlated strongly with echocardiogram reference both at rest and after exercise, giving an R=0.83 and p=3X10-6. Conclusions: We developed a novel method and device that measures cardiac output from exhaled breath, understanding that further validation in heart failure population is needed. This device can be used to measure cardiac output at outpatient settings to improve the quality of care for a great many patients.